2018
DOI: 10.1080/09500340.2018.1502824
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency in Λ-systems of 87Rb atom in magnetic field

Abstract: The electromagnetically induced transparency (EIT) observations in two Λ-systems of 87 Rb atom, |5 2 S 1/2 F = 1 → |5 2 P 3/2 F = 1 ← |5 2 S 1/2 F = 2 and |5 2 S 1/2 F = 1 → |5 2 P 3/2 F = 2 ← |5 2 S 1/2 F = 2 , have been investigated in detail and the results are found consistent with our proposed theoretical models. The second Λ-system provides EIT signal with higher magnitude than the first system, both in absence and in presence of an applied magnetic field. The observed steeper slope of the EIT signal in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…In the absence of the control beams, 'C 1 ' for system (A) and 'C 2 ' for system (B), the transmitted probe signals have shown the expected EIT features of the Λ-systems. As has been reported earlier [38], the EIT signal in system Λ B was observed to be stronger than that in system Λ A . In the presence of control beam, both the systems (N A and N B ) have shown a transmission dip at the center of the existing EIT peak, resulting in splitting of the single EIT peak into two separate EIT peaks i.e.…”
Section: Resultssupporting
confidence: 85%
“…In the absence of the control beams, 'C 1 ' for system (A) and 'C 2 ' for system (B), the transmitted probe signals have shown the expected EIT features of the Λ-systems. As has been reported earlier [38], the EIT signal in system Λ B was observed to be stronger than that in system Λ A . In the presence of control beam, both the systems (N A and N B ) have shown a transmission dip at the center of the existing EIT peak, resulting in splitting of the single EIT peak into two separate EIT peaks i.e.…”
Section: Resultssupporting
confidence: 85%
“…In the absence of the control beams, C 1 for system (A) and C 2 for system (B), the probe transmission have shown the expected EIT features of the Λ-systems. As has been reported earlier [48], the EIT signal in system L B is stronger than that in system Λ A . The transmission is ∼30 % for system Λ A and 50% for system Λ B .…”
Section: T S S S Ssupporting
confidence: 83%
“…3 (a). A detailed study of this Λ system with travelling wave coupling field has been reported in an earlier work [32]. When the retro-reflected coupling beam was passed through the vapor cell to form a standing wave configuration of coupling field inside the atomic medium, the observed transmitted probe beam signal is shown in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In order to establish the supremacy of the EIA signal, a comparison of EIA and EIT signals (in absence and in presence of a magnetic field) was made for different values of power in the coupling field. In one of our earlier studies, it was established that the slope of an EIT signal can be increased by more than two fold by applying an axial magnetic field [32]. Therefore, EIT in presence of magnetic field was included in this comparison.…”
Section: Resultsmentioning
confidence: 99%